2013
DOI: 10.1111/jvim.12161
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D in Dogs with Spirocercosis

Abstract: Background: Spirocercosis in dogs is characterized by esophageal nodules that can undergo neoplastic transformation. Hypovitaminosis D has been associated with neoplasia formation. We hypothesized hypovitaminosis D in neoplastic spirocercosis and that it could be a risk factor for neoplastic transformation. Objective: To measure and compare vitamin D status, assessed by serum 25-hydroxyvitamin D [25(OH)D] concentrations in non-neoplastic (n = 25) and neoplastic (n = 26) spirocercosis client-owned dogs and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…Low vitamin D levels in humans have been associated with a large number of diseases including multiple malignances, cardiovascular and metabolic disorders, autoimmunity and infectious diseases 18, 19, 27 . In veterinary medicine, low vitamin D levels in dogs have been recently linked with chronic enteropathy 28 , neoplasia 29 , and several infectious diseases 30, 31 . The establishment of associations between vitamin D levels and protozoan infections has yielded conflicting results in rodent models 20, 3234 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low vitamin D levels in humans have been associated with a large number of diseases including multiple malignances, cardiovascular and metabolic disorders, autoimmunity and infectious diseases 18, 19, 27 . In veterinary medicine, low vitamin D levels in dogs have been recently linked with chronic enteropathy 28 , neoplasia 29 , and several infectious diseases 30, 31 . The establishment of associations between vitamin D levels and protozoan infections has yielded conflicting results in rodent models 20, 3234 .…”
Section: Discussionmentioning
confidence: 99%
“…Although vitamin D levels have been determined in other canine infectious diseases 30, 31 , no longitudinal studies have been performed so far. The few longitudinal studies conducted in humans reported vitamin D deficiencies prior to clinical manifestations of multiple sclerosis 40 , pulmonary exacerbations in children with cystic fibrosis 41 , and more severe inflammatory bowel disease course 42 .…”
Section: Discussionmentioning
confidence: 99%
“…When the animal has the active disease, it has been linked to a high antibody level and a progressive Th2-deactivating immune response in the presence of a strong inflammatory reac- (Martineau et al, 2007). Considering that hypovitaminosis D is associated with neoplasia and spirocercosis infection may also induce tumoral formation, Rosa et al (2013) developed a study to compare vitamin D status in healthy, neoplastic and non-neoplastic dogs with spirocercosis. Considering that hypovitaminosis D is associated with neoplasia and spirocercosis infection may also induce tumoral formation, Rosa et al (2013) developed a study to compare vitamin D status in healthy, neoplastic and non-neoplastic dogs with spirocercosis.…”
Section: Concentrationsmentioning
confidence: 99%
“…The relationship of vitamin D and diseases has also been investigated in dogs and cats, and some studies found association between low vitamin D status and some types of cancer (Selting, Sharp, Ringold, Thamm, & Backus, 2016;Wakshlag et al, 2011;Weidner et al, 2017), congestive heart failure (Kraus et al, 2014;Osuga et al, 2015), gastrointestinal diseases (Allenspach, Rizzo, Jergens, & Chang, 2017;Gow et al, 2011;Lalor et al, 2014;Titmarsh, Gow, Kilpatrick, Cartwright, et al, 2015;Titmarsh, Gow, Kilpatrick, Sinclair, et al, 2015), acute pancreatitis (Kim et al, 2017), acute polyradiculoneuritis (Laws, Kathrani, Harcourt-Brown, Granger, & Rose, 2018), chronic kidney disease (Cortadellas, Fernandez del Palacio, Talavera, & Bayón, 2010;Galler et al, 2012;Gerber, Hässig, & Reusch, 2003 infectious diseases (Lalor et al, 2012;Rodriguez-Cortes et al, 2017;Rosa, Schoeman, Berry, Mellanby, & Dvir, 2013;. Although these studies do not prove a cause-effect relationship, they provide a basis for future studies to investigate possible positive effects of vitamin D supplementation on improving health status and reducing the risk of developing diseases.…”
Section: Introductionmentioning
confidence: 99%
“…), Spirocerca lupi infections (Rosa et al . ), protein‐losing enteropathy (Mellanby et al . , Gow et al .…”
Section: Vitamin D – An Overviewmentioning
confidence: 99%